Morphological and genetic variabilities of Fusarium species isolated from kenaf - Mohd Zainuddin, Nur Ain Izzati; Z., Mohd Aizat; Mohd Sidique, Siti Nordahliawate; I., Mat Rasid (Malaysian Society of Applied Biology, 2014)
The objectives of this study were to identify the Fusarium species associated with kenaf based on morphological, pathological and genetic characteristics. Twenty isolates of Fusarium were obtained from root, leaf and stem of kenaf in Kuala Terengganu, Malaysia. All Fusarium isolates were identified, and classified into four species such as F. oxysporum, F. proliferatum, F. semitectum and F. solani. Based on pathogenicity test, F. oxysporum was only pathogenic and caused Fusarium wilt disease in kenaf based on disease severity index (DSI), plant height and dry weight of plant. For vegetative compatibility groups (VCGs) study, 217 nitrate non-utilizing (nit) mutants were generated with nit1 was the highest mutants recovered. All the species are genetically diverse reflected from the VCG multiple groups. F. oxysporum isolates were grouped into 5 VCGs, F. proliferatum in 3 VCGs and F. semitectum in 4 VCGs. Fusarium species isolated from kenaf were diverse based on morphology and vegetative compatibility, however only F. oxysporum caused Fusarium wilt disease.